On Nonunique Fixed Point Theorems via Interpolative Chatterjea Type Suzuki Contraction in Quasi-Partial b-Metric Space - Pragati Gautam; Shiv Raj Singh; Santosh Kumar; Swapnil Verma (Journal of Mathematics)
In the present research paper, Chatterjea type contraction is defined and discussed in the framework of quasi-partial b-metric space. Further, some common fixed point results are proved using the notion of interpolation. The results are extended to fixed point theorems for modified Chatterjea type Suzuki contraction using w-admissible maps. The results proved are new and unique supported by application which will enrich the existing literature.